'My' self on camera : first person documentary practice in an individualising China - Yu, Kiki Tianqi (Edinburgh studies in East Asian film., 2019)
This book problematises how the sense of self and subjectivities are understood in contemporary China, and provides illuminating new insights on the changing notion of the individual through cinema.